Ekuitas Merek dan Loyalitas Pelanggan - Arif Rakhman (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
The purpose of this research are to determine the influence of staff service, self-image congruence, and brand awareness on brand satisfaction and attitudinal loyalty, and the influence of brand satisfaction on attitudinal loyalty in three star hotels at Tegal. By using non-probability sampling, this research uses 120 respondents to be the sample. This study uses Structural Equation Modeling (SEM) Sub-Group. The results of this study are staff service, self-image congruence, and brand awareness have significant influence on brand satisfaction and attitudinal loyalty, brand satisfaction has significant influence on attitudinal loyalty.